Therapy of Coronary Heart Disease-Current Standpoint: Conservative Medical Therapy vs PTCA/STENT and CABG (Bypass Sugery) - Strodter, Dietrich (UNI-MED, 2013)
Therapy of Coronary Heart Disease-Current Standpoint: Conservative Medical Therapy vs PTCA/STENT and CABG (Bypass Sugery)